Root Ralan” and Social Adaptation of Local Communities in Overcoming Hunger (Food Scarcity) on Larat Island, Tanimbar Island Regency (KKT) - Paulus Koritelu (Peneliti.net, 2021)
The issue of Poverty that leads to food scarcity (hunger) has never occurred in the history of the Larat Tanimbar people. The determinant of food availability is guaranteed by a local adaptation system on Larat Island called Root Ralan. Root Ralan relates to two very basic aspects, namely: first: Simasali (cooperation), second: Duan Lolat's kinship system and third: traditional food storage system for farm produce. Simasali is a form of cooperation in opening new gardens to harvesting new garden products. Simasali is also internally a reinforcing force from various possible conflicts due to the consequences of rapid social change in this modern era. Duan Lolat implies 3 systems of social relations that show the kinship characteristics of the Larat Tanimbar people, namely: Yaan Warin, Ura Yanan and Kida Bela. The form and function of Root Ralan resembles 3 procedures for storing garden produce according to the form and purpose of storage. Root Ralan is also a reflection of the life system of the Larat Tanimbar people who continue to experience preservation in the midst of the challenges of modernity and globalization today.